2019
DOI: 10.1123/jab.2019-0043
|View full text |Cite
|
Sign up to set email alerts
|

Does Decreasing Below-Knee Prosthesis Pylon Longitudinal Stiffness Increase Prosthetic Limb Collision and Push-Off Work During Gait?

Abstract: Investigations have begun to connect leg prosthesis mechanical properties and user outcomes to optimize prosthesis designs for maximizing mobility. To date, parametric studies have focused on prosthetic foot properties, but not explicitly longitudinal stiffness that is uniquely modified through shock-absorbing pylons. The linear spring function of these devices might affect work performed on the body center of mass during walking. This study observed the effects of different levels of pylon stiffness on indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
3
4
0
Order By: Relevance
“…Such musculoskeletal models may reveal insights that are inaccessible with the current study’s analyses, such as how energy is transferred within the lower extremity (including to and from the prosthesis) due to the dynamic coupling of interconnected segments [ 44 , 45 ]. Altogether, reducing pylon stiffness increased the energy absorption on the total prosthetic limb (summation of prosthesis, knee, and hip) during collision, consistent with a prior study [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Such musculoskeletal models may reveal insights that are inaccessible with the current study’s analyses, such as how energy is transferred within the lower extremity (including to and from the prosthesis) due to the dynamic coupling of interconnected segments [ 44 , 45 ]. Altogether, reducing pylon stiffness increased the energy absorption on the total prosthetic limb (summation of prosthesis, knee, and hip) during collision, consistent with a prior study [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…While not included in our original hypotheses, we found that reducing pylon stiffness reduced collision work on the sound limb, consistent with a prior study [ 32 ]. Individuals with a unilateral amputation typically have greater sound limb collision work compared to healthy control participants [ 26 , 48 ] and has been implied as a potential risk factor for joint osteoarthritis [ 49 51 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations